Effects Use of Information And Technology Learning Communication Toward Students 'Achievement Knowledge Science in Vocational Schools Jakarta - Endang Suparman; Kapraja Sangadji (Peneliti.net, 2020)
This study aims to determine: 1) teachers 'perceptions about the use of ICT, 2) the ability of lecturers to develop ICT, and 3) The effect of lecturers' perceptions about the use of ICT and the ability of lecturers to develop ICT-based learning on student learning. Achievements in science subjects in vocational high schools in Jakarta. This research uses a quantitative approach with a survey method and is carried out in vocational high schools. The population of this study was 290 Senior High School Teachers. Determination of the sample is done by simple random sampling technique. The collection of data in this study uses questionnaires and documents on student learning outcomes. Research data were analyzed using descriptive and inferential statistics. This study concluded that: 1) There was an effect of teacher perceptions about the use of ICT on students' learning achievement in science subject, 3) There was an effect of teacher’s abilities develops ICT-based learning on student’s learning achievement in science subject, and 3) there was a joint effect of teachers’ perceptions about the use of ICT, the ability of teachers to develop ICTs for learning on student’s learning achievement in science subject. Based on the results of this study, it is recommended that to improve students 'ICT learning outcomes should be improved through teacher perceptions about the use of ICT, the ability of teachers to develop ICTs for learning